1998
DOI: 10.1007/s002709900213
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Hemorrhage Due to Duodenal Erosion by a Biliary Wallstent

Abstract: A self-expanding metallic stent (Wallstent) was used to relieve obstruction of the common bile duct in a young male with a desmoplastic small cell tumor of the abdomen. Two months after insertion and following a course of chemotherapy the lower end of the stent eroded the mucosa of the second part of the duodenum causing severe gastrointestinal hemorrhage which necessitated laparotomy and trimming of the stent. This complication may have been due to shrinking of the tumor as well as thrombocytopenia following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Although some authors have suggested that duodenal ulceration and subsequent bleeding or perforation of the duodenum, as well as both reflux of duodenal content into the bile duct (once believed to be a cause of early stent dysfunction) and pancreatitis are complications of the transpapillary method of stent placement, the cases they encountered were limited (12-15). In spite of concerns over these complications, most reports describing the long-term results of metallic stent insertion have demonstrated that their incidence is very low (2, 12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some authors have suggested that duodenal ulceration and subsequent bleeding or perforation of the duodenum, as well as both reflux of duodenal content into the bile duct (once believed to be a cause of early stent dysfunction) and pancreatitis are complications of the transpapillary method of stent placement, the cases they encountered were limited (12-15). In spite of concerns over these complications, most reports describing the long-term results of metallic stent insertion have demonstrated that their incidence is very low (2, 12).…”
Section: Discussionmentioning
confidence: 99%
“…In spite of concerns over these complications, most reports describing the long-term results of metallic stent insertion have demonstrated that their incidence is very low (2, 12). Interestingly, most reports of bleeding involved cases in which the prototype Wallstent was used (15).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of stent-related complications involve stent occlusion, leading to cholangitis. Displacement of the stent in the duodenal wall, which is another complication, is not only associated with occlusion but also with the formation of erosions and ulcers from mechanical irritation, and serious bleeding and gastrointestinal tract perforation [3][4][5] . An intervention for stent occlusion is mechanical cleaning, using devices such as a balloon, but, the occlusion recurs in a comparatively short time in many cases [6] .…”
Section: Introductionmentioning
confidence: 99%
“…Urinary tract obstruction can be palliated by interventional radiology by nephrostomy or antegrade ureteric stenting [34]. Palliation of malignant obstructive jaundice with permanent metallic stents is rarely required in childhood, although there are reports of a few procedures [31,[35][36][37].…”
Section: Other Palliative Proceduresmentioning
confidence: 99%